2018
DOI: 10.1007/s10461-018-2227-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding HIV Risk Behaviors Among Young Men in South Africa: A Syndemic Approach

Abstract: Young men in South Africa experience several adverse socio-structural and psychosocial factors that may contribute HIV risk behaviors. This study applied a syndemic framework to explore whether these syndemic factors are interconnected and work in synergy to increase HIV risk behaviors. Five syndemic factors were assessed including: binge drinking, polydrug use, depressive symptoms, violence and food insecurity on two HIV risk behaviors: multiple sex partners and transactional sex. Participants were (N = 1233)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 59 publications
1
14
0
1
Order By: Relevance
“…Prior research has demonstrated that alcohol use is a mediator of HIV risk taking behaviors such as unprotected sexual activities. [54][55][56] Often used to temporarily relieved symptoms of depression, alcohol use among MSM may similarly mediate viral transmission by providing greater opportunities for cognitive escape. 57 Despite enhancing the risk of transmission by greater than 200%, research has consistently found a negative relationship between levels of drinking and the likelihood of ever testing for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that alcohol use is a mediator of HIV risk taking behaviors such as unprotected sexual activities. [54][55][56] Often used to temporarily relieved symptoms of depression, alcohol use among MSM may similarly mediate viral transmission by providing greater opportunities for cognitive escape. 57 Despite enhancing the risk of transmission by greater than 200%, research has consistently found a negative relationship between levels of drinking and the likelihood of ever testing for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…A quick but thorough search of the scientific literature indicated that there are no studies that identified and characterized syndemics revolving around HIV burdens in sub-Saharan Africa including Kenya except in South Africa [16, 17]. Studies that have been conducted among PWIDs in Kenya have mainly been limited to the assessment of individual risk factors and behaviors associated with HIV incidence and prevalence missing out on the syndemic approach that advances a systems-thinking approach [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions may explain some of the heterogeneity found in the alcohol-IPV association, providing critical understanding on how to effectively intervene and reduce IPV perpetration among men. As both IPV and alcohol use lead to numerous health consequences, including HIV/STI infection, depression, physical injury, and death, IPV and alcohol interventions are urgently needed to improve the health and well-being of men and women at-risk for IPV [ 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of depressive symptoms on the alcohol-IPV relationship is unexplored among men with HIV, a group at high risk for hazardous alcohol use, IPV perpetration, and forward HIV transmission [ 16 , 17 , 28 30 ]. In Vietnam, depressive symptoms are highly prevalent and a known correlate of IPV perpetration among men with HIV [ 31 ].…”
Section: Introductionmentioning
confidence: 99%